Using constructs from the Diffusion of Innovation theory and Consolidated Framework for Implementation Research to evaluate and implement rehabilitation technology in neurologic rehabilitation: A commentary. - Bonner, Sierra; McNair, Keara (Assistive Technology, 2026)
There are no existing guidelines for healthcare teams to evaluate rehabilitation technology and maximize its use in neurologic rehabilitation. By incorporating rehabilitation technologies into neurorehabilitation, therapists can bridge the gap between research and feasible client-centered interventions. Technology use can facilitate evidence-based practice that reflects recent trends in neurorehabilitation. Integration of rehabilitation technology is heavily dependent on the consideration of the barriers to technological adoption at both the organizational level and clinical level. The purpose of this commentary is to describe a theory-driven, systematic process with consideration of facilitators and barriers to technological uptake in neurorehabilitation. This process considers the views of multiple stakeholders to evaluate technology in rehabilitation and make cost-effective decisions, maximize available interventions, prevent technological abandonment, and integrate evidenced-based interventions for neurorehabilitation best practice.